Molecular dynamics reveal potential effects of novel VHL variants on VHL-Elongin C binding in ccRCC patients from Eastern India - Srilagna Chatterjee; Nirvika Paul; Anwesha Das; Sarbashri Bank; Biswabandhu Bankura; Ravi Prakash Yadav; Kunal Sarkar; Soumen Saha; Subhajit Malakar; Sunirmal Choudhury; Sudakshina Ghosh; Madhusudan Das (Scientific Reports)
Abstract Renal cell carcinoma (RCC) is the one of the most fatal and frequent form of urological malignancy worldwide. The von Hippel-Lindau (VHL) tumour suppressor gene is a critical component of the VHL-Cullin2-ElonginB/C (VCB) complex that regulates the ubiquitin-mediated proteasomal degradation of proteins with mutations consistently associated with the development of clear cell renal cell carcinoma (ccRCC). Despite extensive investigations conducted worldwide, there is a notable lack of data concerning VHL mutations in sporadic ccRCC patients from India. Our study aimed to investigate the sporadic VHL mutations within the tumours of 210 ccRCC patients without a familial history of VHL disease. We extracted genomic DNA from tumour and adjacent normal tissues, PCR amplified and sequenced the VHL gene. In silico tools were used assess the damaging potential of missense variants on pVHL structure and stability. Protein-protein docking and protein flexibility molecular docking simulation study were employed to study the interaction between wild-type and mutated VHL models with Elongin C. Sequence analysis revealed seven novel missense mutations in patient tumour tissues p.(Val170Phe), p.(Arg69Cys), p.(Phe76Leu), p.(Glu173Asp), p.(Leu201Val), p.(His208Leu), p.(Arg205Pro). I-Mutant 2.0 indicated these mutations reduced pVHL stability (ΔΔG < -0.5 kcal/mol). Protein Flexibility-Molecular Dynamic (MD) Simulation study indicated that mutations weaken the interaction of VHL with Elongin C, with V170F showing the most significant reduction in binding quality and stability. In conclusion, this study introduces novel genetic data from an understudied population and highlights the impact of VHL mutations on its interaction with Elongin C. These findings contribute to our understanding of the molecular basis of VHL-related pathologies and may guide future therapeutic strategies targeting these interactions.